Respuesta :
The you used was number 6 here why
First you need to do is figure out the full equation as written in the question.
What I did is this:
x=starting number
3x multiply by 3
3x-8 subtract by 8
2(3x-8) double the result
2(3x-8)+14 add 14
2(3x-8)+14+.5(2(3x-8)+14) add half of result
2(3x-8)+14+.5(2(3x-8)+14)-11 subtract 11
2(3x-8)+14+.5(2(3x-8)+14)-11/5=8 divide entire equation by 5 to get the answer of 8
Now, solve!
multiply both sides by 5:
2(3x-8)+14+.5(2(3x-8)+14)-11=40
next thing we want to do is get rid of the first set of parenthesis:
6x-16+14+.5(6x-16+14)-11=40
now get rid of second set of parenthesis:
6x-16+14+3x-8+7-11=40
combine like terms:
(6x+3x)+(-16+14-8+7-11)=40
9x-14=40
add 14 to both sides:
9x=54
divide by 9:
x=6
Now, lets check the answer!
6*3=18-8=10*2=20+14=34+17=51-11=40/5=8
We got the original final answer so your original number was 6!